Disagreement à la Taylor: Evidence from survey microdata - Lena Dräger; Michael J. Lamla (Hamburg University, Department Socioeconomics, 2015)
There is a growing interest in studying the disagreement of economic agents. Most studies, however, focus on the disagreement regarding one specific variable, hereby neglecting that disagreement may be comoving with disagreement on other variables. In this paper we explore to which extent disagreement regarding the interest rate is driven by disagreement on inflation and on unemployment. This relationship can be motivated by the existence of the Taylor rule. Using micro survey data for both professional forecasters and consumers, we provide evidence that disagreement on the future interest rate is mainly driven by disagreement on inflation. Exploring further determinants, we confirm that central bank transparency as well as news on money and credit conditions significantly influence disagreement.
Keywords: E31; E58; D84; C33; 330; disagreement; inflation expectations; microdata